Analysis of the Main Structural Characteristics of the Romanian Financial System - Marius Constantin Apostoaie (CES Working Papers, 2011)
To know and to understand the factors within a financial system that significantly influences the institutions behaviour and the market responses to the central bank actions is of great importance for the monetary authorities and for the achievement of their monetary policy objectives. In Romania, the National Bank must pay special attention to financial institutions given their significant role in the process of financial intermediation (bank-based system). This study aims to conduct an investigation of the main coordinates of the Romanian financial system that are relevant for the study of the monetary policy transmission mechanism. The study focuses on the following features of the Romanian financial system: financial deepening, the existence of a bank-based system, the concentration degree of the Romanian banking sector, the balance sheet structure of monetary financial institutions and the soundness of the banking system. The study also considers the effects of the recent financial market turmoil on the financial system. The span of the empirical study covers the period after 2000 but brings to the forefront the period before and after October 2008. We believe that this research provides useful information for a future analysis of the Romanian monetary policy transmission mechanism.
Keywords: E50; G21; 330; financial system; banking system; Romania; monetary policy transmission mechanism Romania